African American English (AEE) And Slang Used by Jim and Huck Finn in The Adventures of Huckleberry Finn (Universitas Islam Negeri Sunan Ampel Surabaya, 2014)
African American English and slang are now become interesting topics among linguists for its unique characteristics and usage in daily society as vernacular language. This paper analyses the use of African merican English and slang used by an African American and a Caucasian American in The Adventures of Huckleberry Finn novel. Findings propose that African American English and slang are particulary used by African American speakers as their daily language, but non African Americans may choose this variety as their language choice.